The meaning and content of national (state) idea of Kazakhstan (Journal of Philosophy Culture and Political Science, 2018)
This article is considered problems and some scientific aspects of formation of a national (state) idea of Kazakhstan. To determine the nature and content of the national (state) idea of Kazakhstan authors analyzed different opinions of our scientists. The formation of the national idea of the state is one of the most controversial topics in today’s political science. It is defined relevance in shaping public ideas in poliethnical country as Kazakhstan. It is also defined   that the interests and ethnic groups can develop and shape goverment’s idea through public policy. Key words: national idea, state idea, state policy, ideology, interethnic harmony.